Pathways to sustainable transitions in a complex agricultural system: a case study of swine waste management in North Carolina - Deviney, Alison V.; Classen, John J.; Bruce, Jacklyn A. (Frontiers in Sustainable Food Systems, 2024)
North Carolina has a high density of swine farms with nearly half of the commercial operations located in two eastern counties. Lagoon and sprayfield (LS) is the dominant method of swine manure management despite pressure to transition to environmentally superior technologies. LS is an efficient and cost-effective method of waste management but has negatively impacted the environment and local communities from both discreet events (breeches, flooding) and ongoing issues (odor, disease vectors). The Multilevel Perspective Theory (MLP) is a frame for understanding the relationships between a sociotechnical regime, its surrounding landscape, and emerging niches for sustainable technology development to help align these different levels of perspective and support transitioning toward more sustainable practices. Here, a farm level is added to represent the user perspective of regime technology in complex agriculture systems (MLP + F). We demonstrate how change may influence the North Carolina swine waste management (NC SWM) system through alternative scenarios applied to a conceptual model developed with the MLP + F frame in a methodology for analyzing complex agricultural systems with input from a diverse panel of experts. This case study demonstrates how the methodology can be applied through two NC SWM model scenarios analyzed with fuzzy cognitive mapping techniques. The first scenario explores whether panel recommended changes generate a shift toward sustainable manure management. Inference results suggest that experts have a broad understanding of how these goals may be achieved, but strategies are needed to enhance the specificity of proposed changes. Testing scenarios with more targeted interventions within specific subsystems could provide greater guidance with regard to policy, economic factors, farm practices, or societal demands. The second scenario considers the systemic effect of introducing a manure dewatering process on swine operations, with and without landscape support. Results from this scenario indicate that the more landscape support is engaged, the greater the impact on desirable outcomes. However, contradictions emerged between different versions of this scenario such as increased negative public perceptions despite positive community outcomes. This may require further investigation to tease out potential misalignment between perceptions of a complex system and actual system behaviors.